Integrating Lean Practices and IT Governance Capabilities for Enhancing Smart Manufacturing Performance: An Empirical Framework from the Industrial Engineering Perspective - Kordian, Zahra; Haj Khan Mirzay Sarraf, Ebrahim; Golestaneh, Ramin (International journal of industrial engineering and operational research, 2026)
The swift evolution of Industry 4.0 technologies has significantly altered the operational framework of manufacturing companies, compelling them to pursue both process excellence and robust digital governance concurrently. While lean manufacturing has demonstrated effectiveness in removing non-value-adding activities and enhancing operational efficiency, the contribution of information technology (IT) governance in bolstering these advancements is still inadequately examined in the industrial engineering literature. This research aims to fill this void by proposing and empirically validating a comprehensive framework that integrates lean practices with IT governance capabilities to improve smart manufacturing performance. Based on the principles of lean manufacturing, IT governance, and digital transformation, the proposed framework investigates how aligning technological resources with operational goals leads to better manufacturing results. A sequential mixed-methods approach was utilized. Initially, a Delphi panel comprising academic experts and seasoned industry professionals was convened to refine the conceptual dimensions of the framework and ensure content validity. Following this, survey data were gathered from 178 manufacturing firms across various industrial sectors and analyzed using structural equation modeling (SEM) to evaluate the proposed relationships. The empirical results indicate that lean practices have a substantial positive impact on smart manufacturing performance. Additionally, IT governance capabilities partially mediate this relationship by promoting strategic alignment, enhancing decision-making quality, and improving the effective use of digital resources. The findings also highlight top management commitment, cross-functional collaboration, and real-time data analytics capability as essential success factors that facilitate the implementation of the integrated framework. This research enhances the current body of knowledge by connecting two historically distinct fields—industrial engineering and IT governance—while presenting a thorough viewpoint on value generation within smart manufacturing settings. Practically, the suggested framework equips managers with a quantifiable guide for synchronizing technology expenditures with operational enhancement efforts, thus promoting agile, resilient, and data-informed manufacturing systems that can maintain a competitive edge in the digital age.